Analisis Bahaya Arc-Flash pada Sistem Distribusi Industri Menggunakan ETAP Berbasis IEEE 1584-2018 - Gilbert Sarda Sinaga; Alfredo Sibarani; Hudai Hasnandi; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The reliability and safety of industrial electrical power systems have become paramount priorities given the serious threats posed by arc-flash phenomena, which can cause severe injuries, equipment damage, and operational disruptions. This study aims to analyze arc-flash hazards in multi-bus industrial distribution systems using ETAP software based on IEEE 1584-2018 standards. The research methodology employs an experimental simulation design by constructing a distribution system model encompassing bus components, transformers, transmission lines, and protective devices. The analysis focuses on three critical points: Bus 4, Bus 6, and Bus 7. Simulation results indicate that Bus 4 exhibits the highest incident energy of 56.52 cal/cm² with an arc-flash boundary of 5.324 m (NFPA 70E category F), Bus 6 generates 45.90 cal/cm² with a boundary of 4.663 m (category F), and Bus 7 produces 34.40 cal/cm² with a boundary of 3.880 m (category E). The findings underscore the necessity for implementing high-level personal protective equipment, optimizing protection coordination to reduce fault clearing time, and conducting periodic evaluations of protection systems to enhance operator safety and the reliability of industrial distribution systems.